2012
DOI: 10.1063/1.4721521
|View full text |Cite
|
Sign up to set email alerts
|

In situ study of self-assembled GaN nanowires nucleation on Si(111) by plasma-assisted molecular beam epitaxy

Abstract: International audienceNucleation of GaN nanowires grown by plasma-assisted molecular beam epitaxy is studied through a combination of two in situ tools: grazing incidence x-ray diffraction and reflection high energy electron diffraction. Growth on bare Si(111) and on AlN/Si(111) is compared. A significantly larger delay at nucleation is observed for nanowires grown on bare Si(111). The difference in the nucleation delay is correlated to a dissimilarity of chemical reactivity between Al and Ga with nitrided Si(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
56
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 40 publications
3
56
0
3
Order By: Relevance
“…3(c)). Qualitatively, such RHEED pattern evolution is similar to creation of crystalline silicon nitride and its subsequent amorphization as observed by Hestroffer et al 10,14 So different RHEED images in Figs. 3(a) and 3(c) indicate different microstructures of surfaces on which GaN NWs grow.…”
Section: Resultssupporting
confidence: 54%
See 2 more Smart Citations
“…3(c)). Qualitatively, such RHEED pattern evolution is similar to creation of crystalline silicon nitride and its subsequent amorphization as observed by Hestroffer et al 10,14 So different RHEED images in Figs. 3(a) and 3(c) indicate different microstructures of surfaces on which GaN NWs grow.…”
Section: Resultssupporting
confidence: 54%
“…10 Slower nucleation and lower density of NWs were observed on partially amorphous silicon nitride films while no growth of GaN NWs was found on crystalline sapphire substrate under the same growth conditions. HRTEM studies of annealed sapphire and EDX studies of GaN/Al 2 O 3 interface excludes local conversion of amorphous Al 2 O 3 under the nitrogen flux into AlN that would speed up nucleation of GaN nanowires.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…While NWs on a silicon substrate consist of a desirable platform for low-cost and scalable devices, the spontaneous formation of the insulating SiN x layer at the semiconductor/substrate interface limits their applicability, impeding heat dissipation and electrical conduction. 16 It has been recently demonstrated that the NW growth on metal thin films helps to avoid such issues, hence reducing the potential barrier for carrier flow and allowing increased current injections with lower Joule heating. [17][18][19][20][21] As many efforts have been made in the UV III-nitride NW community to bring NW technology to a practical application, it is of particular importance to study the diode T j of such devices to evaluate the best configuration for efficient heat dissipation through the heat sink substrate, prevent overheating, short lifespan, and reduced light intensity.…”
Section: Introductionmentioning
confidence: 99%
“…The development of two-dimensional (2D) X-ray detectors has facilitated the in situ XRD studies of strain relaxation during heteroepitaxy, [39][40][41][42][43][44][45][46][47] NW growth, [48][49][50][51][52][53] and QD growth. [54][55][56][57][58][59][60][61][62] One of the advantages of XRD as an in situ tool is its wide application range as a consequence of the weak interaction of X-rays with matter.…”
Section: Introductionmentioning
confidence: 99%